2021
DOI: 10.3390/ijerph18042008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Food Additive Titanium Dioxide on Gut Microbiota Composition, Microbiota-Associated Functions, and Gut Barrier: A Systematic Review of In Vivo Animal Studies

Abstract: Background: Titanium dioxide (TiO2) is used as a food additive in pastries, sweets, and sauces. It is recognized as safe by food safety authorities, but in recent years, governments and scientists have raised concerns about its genotoxicity. This systematic review aims to assess the potential associations between food TiO2 exposure and microbiota composition and functions. Methods: A systematic literature search was performed up to December 2020 in PubMed, Web of Science, and Scopus databases. The PRISMA guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 64 publications
1
8
0
2
Order By: Relevance
“…One explanation for the high percentage of Firmicutes seen in this study might be the presence of titanium dioxide (TiO 2 ), used as an inert digestibility marker in all finisher diets. This assumption agrees with other studies also indicating an increased abundance of Firmicutes in rodents in the presence of TiO 2 [49]. Although the effects of TiO 2 nanoparticles on gut microbiota and its metabolism have been discussed extensively, the precise mechanisms of these effects are still not elucidated [50].…”
Section: Discussionsupporting
confidence: 89%
“…One explanation for the high percentage of Firmicutes seen in this study might be the presence of titanium dioxide (TiO 2 ), used as an inert digestibility marker in all finisher diets. This assumption agrees with other studies also indicating an increased abundance of Firmicutes in rodents in the presence of TiO 2 [49]. Although the effects of TiO 2 nanoparticles on gut microbiota and its metabolism have been discussed extensively, the precise mechanisms of these effects are still not elucidated [50].…”
Section: Discussionsupporting
confidence: 89%
“…There are very few valuable research results, and there are still many uncertain ecological security issues to be further investigated. Based on the summary of relevant research at home and abroad, the source of nanomaterials, the way of entering the environment, environmental behavior, ecotoxicological research status, and the contents to be further investigated were briefly reviewed [ 3 ]. The development process of nanotechnology is shown in Figure 3 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies have found evidence of downstream events outside the gastrointestinal tract, sharing the same mechanism of absorption through capillaries and vessels, entering the circulatory system with subsequent systemic diffusion [ 32 , 49 , 50 , 51 ]. Therefore, in the present study, we investigated the potential effects of single systemic over-exposure to E171 in immunocompetent healthy mice.…”
Section: Discussionmentioning
confidence: 99%